Regulating the right to health in national laws and international rules - Abdul Aziz Mohammed Al-Madani, Lecturer Ola (The college of law and political science journal, 2023)
Conclusion The right to health enjoys great importance within the scope of theinternal laws, as it was regulated in the constitution and the ordinary laws issuedin Iraq. Also, international laws have given this right great attention because of itsimpact on every individual in this world, but the regulation of the right to health inIraq It did not reach the required level according to international standards, andthe Iraqi citizen continued to suffer from the poor quality of the health servicesprovided